BS EN 4890 AMD 1. Aerospace series. Steel X4CrNiMo16-5-1. Air melted. Hardened and tempered. Sheets and plates. 0, 3 mm ≤ a ≤ 50 mm. 900 MPa ≤ Rm ≤ 1 050 MPa. (27th June 2023) - British Standards Institution,
No abstract available